WHAT I LEARNT: MOBA GAME IN IMPROVING STUDENTS’ SPEAKING ABILITY OF SENIOR HIGH SCHOOL, INDONESIA - Arismunandar (La Parole : Journal of Language Teaching and Pedagogy, 2021)
This research was conveying the influencing MOBA game in the teaching and learning process. This research has two intentions were: 1) influence of MOBAenhance the ability of students to speak, and 2) students’ interest in the use of MOBAgame. This research used a mixed-method. This research’s population was ten classes of the Eleventh grader at SMA Negeri 3 Sidenreng Rappang by population total were 298 students. The research’s sample was XI IPA2(33 students) which got by using a cluster randomly. This research used two varieties of instruments were speaking testand questionnaire. This study found that the influence of MOBA in clarifying thespeaking ability was improving. The mean score of post-test evidenced was higher than pre-test (69.39>51.81). So the researcher stated H0 was refused and H1 was confirmed. Furthermore, this research also found that the Eleventh grader wasinterested in learning speaking where was proved by the questionnaire’s mean score was 79.72 were classified in an interesting category